2015
DOI: 10.15376/biores.10.3.5317-5329
|View full text |Cite
|
Sign up to set email alerts
|

Physical Behavior of Hydro-thermally Treated Oil Palm Wood in Different Buffered pH Media

Abstract: aThis study investigated changes in the physical properties of oil palm (Elaeis guineensis) wood (OPW) using various buffered media for the hydrothermal treatment process. The buffered media were prepared separately for three different treatment conditions: pH of 8, pH of 5, and tap water. These treatments were compared with unbuffered, control samples. The OPW samples were taken from the outer part of the trees. The OPW samples were treated with the buffered media at a temperature of 140 °C for 120 min. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The findings were in agreement with Saliman et al [9] who reported that the oil palm wood hydrothermally treated in alkaline medium exhibited lower TS than the samples treated in acidic medium. Ebadi et al [13] also reported the highest anti-swelling efficiency (ASE) was observed in oil palm wood treated using buffered medium having pH of 8.…”
Section: Resultsmentioning
confidence: 92%
“…The findings were in agreement with Saliman et al [9] who reported that the oil palm wood hydrothermally treated in alkaline medium exhibited lower TS than the samples treated in acidic medium. Ebadi et al [13] also reported the highest anti-swelling efficiency (ASE) was observed in oil palm wood treated using buffered medium having pH of 8.…”
Section: Resultsmentioning
confidence: 92%
“…Ebadi et al [ 37 ] conducted a study on the physical behavior of hydrothermally treated oil palm wood ( Elaeis guineensis Jacq.) in different buffered pH media.…”
Section: Hydrothermal Modification Of Woodmentioning
confidence: 99%
“…Hence, following the removal of extractives and starch from the structure of wood, their high solubility in aqueous solutions, weight loss (WL), and decrease of wood density (WD) appears explainable as well (Talaei and Yaghoobi 2009;Talaei et al 2013). In addition, the ability for buffering of the treatment medium after relatively severe thermal treatment (140 °C) because of the buffer solutions' pH reduction and the release of larger values of organic acids decreased and thus the amount of deacetylation increased (Talaei 2010;Talaei et al 2013;Ebadi et al 2015Ebadi et al , 2016. Therefore, pH of treatment medium decreased with increasing temperature from 80 °С to 140 °С due to the release of large amounts of organic acids (Talaei and Karimi 2012b).…”
Section: Effects Of Buffered Solutions On Treated Responses Weight Loss/mass Loss Response Functionmentioning
confidence: 99%
“…Therefore, pH of treatment medium decreased with increasing temperature from 80 °С to 140 °С due to the release of large amounts of organic acids (Talaei and Karimi 2012b). The neutral buffer may also have an inhibitory effect through the control and neutralization of the acidity (pH) medium at a specified pH level (Talaei 2010;Ebadi et al 2015). In the neutral and alkaline buffers, due to the neutralization of the acidic medium, the amount of acidic hydrolysis caused by the destruction of carbohydrates and ML is less (Talaei et al 2013).…”
Section: Effects Of Buffered Solutions On Treated Responses Weight Loss/mass Loss Response Functionmentioning
confidence: 99%
See 1 more Smart Citation